New life in the wasteland 2 Corinthians on the cost and glory of Christian ministry - Kelly, Douglas F. (Fearn, Scotland Christian Focus, 2003)
Includes bibliographical references.
Keywords: Bible. N.T. Corinthians, 2nd -- criticism, interpretation, etc